Consumer trust in Google's top developers' apps: an exploratory study. (14th November 2016) - Harris, Mark A.; Chin, Amita G.
Abstract : Purpose: This paper aims to investigate Google's top developers' apps with trust badges to see if they warrant an additional level of trust and confidence from consumers, as stated by Google. Design/methodology/approach: Risky app permissions and in-app purchases (IAP) from Google's top developers and traditional developers were investigated in several Google Play top app categories, including Editor's Choice apps. Analysis was performed between categories and developer types. Findings: Overall, Google's top developers' apps request more risky permissions and IAP than do traditional developers. Other results indicate that free apps are more dangerous than paid apps and star ratings do not signify safe apps. Research limitations/implications: Because of a limited number of Google's top developers and Editor's Choice apps, conclusions are drawn from a small sample of apps and not the entire market. Practical implications: Google's top developers' apps are suited well for increasing revenue for Google and developers at the consumer's expense. Consumers should be wary of top developer trust badges. Social implications: As the lure for "top free" and "top developer" software is strong among consumers, this research contributes to societal welfare in that it makes consumers aware that Google top developer app trust badges and free apps are more dangerous than traditional developer and paid apps, as they request risky permissions at a much higher frequency. Therefore, consumers should be very careful when downloading apps that are advertised as "top free" or "top developer". Originality/value: Google's top developers' apps and Editors' Choice apps have not been investigated from the perspective of permissions and IAP before.